2016
DOI: 10.1556/0806.44.2016.026
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield of durum wheat as affected by waterlogging at tillering

Abstract: Waterlogging is one of the limiting factors influencing durum wheat (Triticum durum L.) production. In this paper we investigated the impact of seven waterlogging durations of 4, 8, 12, 16, 20, 40, and 60 days, imposed at 3-leaf and 4-leaf growth stages, on grain yield, grain yield components, straw and root dry weight and nitrogen concentration of grain, straw, and roots of two varieties of durum wheat. Grain yield of both varieties showed a significant reduction only when waterlogging was prolonged to more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 21 publications
7
42
1
Order By: Relevance
“…However, the root, straw, and grain biomass recorded at maturity were significantly lower than in the controls even with the shortest exposure, thus demonstrating that plants of A. sativa and A. byzantina were permanently damaged when they experienced a 7-day or longer waterlogging at tillering combined with spring temperatures. The current data contrast with our previous findings on barley and wheat, which showed reduced biomass and grain yield only after 16 and 20 days of waterlogging (Masoni et al, 2016; Pampana et al, 2016; Arduini et al, 2016a), and with those of Cannell et al (1985) and Watson et al (1976), who found that oats waterlogged at tillering recovered better than other cereals. In all these studies, waterlogging was imposed at the same growth stage as in our study, i.e., tillering, but the sowing was performed in autumn, while in the present study, it was performed in early spring conditions.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the root, straw, and grain biomass recorded at maturity were significantly lower than in the controls even with the shortest exposure, thus demonstrating that plants of A. sativa and A. byzantina were permanently damaged when they experienced a 7-day or longer waterlogging at tillering combined with spring temperatures. The current data contrast with our previous findings on barley and wheat, which showed reduced biomass and grain yield only after 16 and 20 days of waterlogging (Masoni et al, 2016; Pampana et al, 2016; Arduini et al, 2016a), and with those of Cannell et al (1985) and Watson et al (1976), who found that oats waterlogged at tillering recovered better than other cereals. In all these studies, waterlogging was imposed at the same growth stage as in our study, i.e., tillering, but the sowing was performed in autumn, while in the present study, it was performed in early spring conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…Both have medium-early growth cycles, medium-height, and a good resistance to lodging. In previous experiments carried out on wheat, durum wheat, and barley sown in autumn, we found that plants showed grain yield reductions when exposed to waterlogging at the tillering stage for more than 16 days (barley) and 20 days (wheat and durum wheat) (Masoni et al, 2016; Pampana et al, 2016; Arduini et al, 2016a). In the present study, we expected that the higher temperatures during waterlogging, imposed by the later sowing, would increase plant sensitivity at tillering.…”
Section: Methodsmentioning
confidence: 88%
“…Only some studies have analyzed the impact of waterlogging throughout the entire plant life-cycle, describing responses in vegetative growth and seed production. As examples: in wheat, 20 days of waterlogging on 3–4 leaf-stage plants resulted in a final dry mass and yield representing 95 and 90% of controls, respectively (Collaku and Harrison, 2002; Pampana et al, 2016a); in barley, plants attained 85 and 90% of controls in dry mass and yield when waterlogged for 20 days at 3–4 leaf-stage (Masoni et al, 2016); in rapeseed, 21 days of soil hypoxia, applied to 5-leaf stage plants, constrained growth as the stressed individuals attained 77% in dry mass and 73% in yield compared to the control (Leul and Zhou, 1998); in field pea, 5 days of waterlogging had a substantial impact on plant dry mass accumulation and seed production as, respectively, stressed plants attained 35–50% and 5–25% of controls (Jackson, 1979; Pampana et al, 2016b). Nevertheless, information on root and shoot growth rates during waterlogging and subsequent recovery is scarce, and studies to functionally link leaf physiological responses with growth (i.e., RGR) and seed production (but see Li et al, 2011 for wheat are few).…”
Section: Introductionmentioning
confidence: 99%
“…These responses were likely due to the short duration of flooding more than to the activation of other adaptive systems (e.g. aerenchyma, Dennis et al, ), as supported by the findings of Pampana et al () who reported a reduction of grain yield of two varieties (Claudio and Svevo) only when waterlogging was prolonged for more than 20 days. Although O 3 and flooding are similarly able to induce oxidative stress in plants (Mustroph, ; Sandermann, ), our data show that the phenolic response to these environmental constraints is stress specific, with a higher activation induced under O 3 than under flooding, another aspect to take into account when breeding future cultivars.…”
Section: Discussionmentioning
confidence: 72%
“…In most of these areas, durum wheat have commonly to cope with major climatic constraints, mainly elevated temperatures, drought and high O 3 levels, but also flooding (this is expected to increase in the near future). Most of available literature concerns O 3 effects on common wheat (T. aestivum L.), although durum wheat is also known to be both O 3 (Fangmeier, Brockerhoff, Grüters, & Jäger, 1994;Ollerenshaw & Lyons, 1999;Picchi, Francini, Nali, & Lorenzini, 2006) and flooding sensitive (Burgos, Stamp, & Schmid, 2001;Pampana, Masoni, & Arduini, 2016), even if somewhat contrasting results have been reported based on genotypic differences in tolerance and on intensity and duration of the stress exposure (Gerosa et al, 2014;Mustroph, 2018;Pampana et al, 2016).…”
mentioning
confidence: 99%